2011
DOI: 10.1111/j.1365-2486.2011.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil moisture on the temperature sensitivity of heterotrophic respiration vary seasonally in an old‐field climate change experiment

Abstract: Microbial decomposition of soil organic matter produces a major flux of CO2 from terrestrial ecosystems and can act as a feedback to climate change. Although climate‐carbon models suggest that warming will accelerate the release of CO2 from soils, the magnitude of this feedback is uncertain, mostly due to uncertainty in the temperature sensitivity of soil organic matter decomposition. We examined how warming and altered precipitation affected the rate and temperature sensitivity of heterotrophic respiration (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
261
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(302 citation statements)
references
References 80 publications
24
261
4
1
Order By: Relevance
“…Our study indicated that short-term apparent Q 10 of SR and MR had a clear seasonality, which is consistent with the recent results of Jia et al (2013) and Suseela et al (2012). Jia et al (2013) found that short-term Q 10 was higher in the beginning of the growing season in a Chinese pine (Pinus tabulaeformis) plantation.…”
Section: The Seasonal Variation Of Short-term Apparent Q 10 Of Sr and Mrsupporting
confidence: 81%
See 3 more Smart Citations
“…Our study indicated that short-term apparent Q 10 of SR and MR had a clear seasonality, which is consistent with the recent results of Jia et al (2013) and Suseela et al (2012). Jia et al (2013) found that short-term Q 10 was higher in the beginning of the growing season in a Chinese pine (Pinus tabulaeformis) plantation.…”
Section: The Seasonal Variation Of Short-term Apparent Q 10 Of Sr and Mrsupporting
confidence: 81%
“…Despite numerous studies, the temperature sensitivity of MR remains controversial Kirschbaum 2006;Hakkenberg et al 2008). For example, Suseela et al (2012) found the temperature sensitivity of heterotrophic respiration was unresponsive to warming treatments; however, a reduction of the temperature sensitivity of soil organic matter decomposition with sustained temperature increasing was reported by Craine et al (2013). The causes of this controversy may stem from confounding controlling factors such as soil moisture and substrate availability Kirschbaum 2006).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moisture and temperature interactions have been observed in a number of experimental studies (Craine and Gelderman, 2011;Rey et al, 2005;Suseela et al, 2012;Wickland and Neff, 2008), but neither consistent trends 30 nor general explanatory theories have been identified. Improving our understanding of these interactions is a crucial step in increasing confidence in models and for interpreting modelling and experimental results (Crowther et al, 2016;Tang and Riley, 2014).…”
Section: Introductionmentioning
confidence: 98%